Residual welding stress of I-section members beyond the limits of width-thickness ratio - Zhiyuan Li; Zhiyun Zhao (Fracture and Structural Integrity)
Despite the extensive studies on the effect of width-thickness ratio and residual stress on member behavior, few scholars have probed into the residual stress distribution on the I-section members. Based on the principle of blind hole drilling, this paper conducts an experimental study of the residual welding stresses of eight welded I-shaped members. Through the analysis of the test results, the author draws the following conclusion: it is safe to use I-section members beyond the limits of width-thickness ratio because the residual stress distribution is not severely affected by width-thickness ratio.